Serotonin Syndrome in Critical Care - Daniel Miller DO; Deesha Shah MD; John Huribal MD; Skye Felice DO; Theo Trandafirescu MD (SAGE Publishing, 2023)
Serotonin syndrome is a life-threatening syndrome that can occur when medications or drugs that cause serotonergic activity are taken. Frequently this syndrome is caused using 2 serotonergic medications at once or switching from 1 serotonergic medication to another without tapering appropriately. The classic triad of serotonin syndrome is neuromuscular excitability, autonomic dysfunction, and altered mental status. Patients can have symptoms ranging from tachycardia, diaphoresis, fever, and hypertension to severe swings in blood pressure, tremors, hyperreflexia, muscle rigidity, and even death. Most patients admitted to the hospital with fevers, tachycardia with hypertension, or hypotension will have blood cultures drawn as infection can easily explain these symptoms. If these symptoms persist, however, other options should be explored, including serotonin syndrome.